2002
DOI: 10.4141/a01-069
|View full text |Cite
|
Sign up to set email alerts
|

The effect of spring turnout date on weight gain by cattle on native pasture

Abstract: . 2002. The effect of spring turnout date on weight gain by cattle on native pasture. Can. J. Anim. Sci. 82: 575-585. The effect of early turnout on pasture quality and weight gain by beef cattle was assessed with 32 Hereford feeder cattle which were turned out on pasture on four separate dates in each of 2 yr in a randomized complete block design with two replications. In 1998, steers were allocated to four treatments numbered consecutively T1 to T4 according to turnout date: 6 May [110 growing degree days ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…In year 1, even though pasture availability and quality were non-limiting and cattle had been backgrounded at 0.5 to 0.6 kg d -1 before turnout, they lost 16 kg BW and required almost 16 d to regain their turnout weight. These losses are similar to those reported in the literature for cattle previously gaining 0.5 to 1.0 kg d -1 (Nicholson 1980;Kyne et al 2001;Jannasch et al 2002). In year 2, cattle had been gaining up to 0.9 kg d -1 during confinement and this should have increased the extent of weight loss at turnout.…”
Section: Sward Characteristics and Weight Loss By Cattlesupporting
confidence: 78%
See 1 more Smart Citation
“…In year 1, even though pasture availability and quality were non-limiting and cattle had been backgrounded at 0.5 to 0.6 kg d -1 before turnout, they lost 16 kg BW and required almost 16 d to regain their turnout weight. These losses are similar to those reported in the literature for cattle previously gaining 0.5 to 1.0 kg d -1 (Nicholson 1980;Kyne et al 2001;Jannasch et al 2002). In year 2, cattle had been gaining up to 0.9 kg d -1 during confinement and this should have increased the extent of weight loss at turnout.…”
Section: Sward Characteristics and Weight Loss By Cattlesupporting
confidence: 78%
“…A possible negative impact of early turnout is increased poaching and soil compaction. In a related study, Jannasch et al (2002) found no effect of turnout date on soil compaction. In year 2, we tried to evaluate the effect of turning cattle out either just before or just after the anticipated "spring flush" of grass by having two turnout dates.…”
Section: Sward Characteristics and Weight Loss By Cattlementioning
confidence: 99%
“…Jannasch et al (2002) found that earlier turnout date had inconsistent results -one year showed no significant effects, and one year showed cattle weight actually decreasing with earlier turnout date. Similarly, Charmley et al (2003) found that earlier turnout date decreased weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Charmley et al (2003) and Jannasch et al (2002) found that earlier turnout date decreased weight gain, while Steen (2002) found the opposite. In order to resolve these contradictions it is important to elucidate the mechanism of the effect of turnout date.…”
mentioning
confidence: 99%
See 1 more Smart Citation